Fine-grained detection of land use and water table changes on organic soils over the period 1992⿿2012 using multiple data sources in the Drömling nature park, Germany. (30th November 2016) - Untenecker, Johanna; Tiemeyer, Bärbel; Freibauer, Annette; Laggner, Andreas; Braumann, Fred; Luterbacher, Juerg
Highlights: ⿢ We developed a ⿿soft translation key⿿ to combine different land use (LU) datasets. ⿢ We generated LU time-series suitable for Kyoto accounting on organic soils. ⿢ LU in the ⿿Drömling⿿ nature park became less intensive. ⿢ LU time-series are a semi-quantitative proxy for groundwater depth. Abstract: The construction of consistent time series of land use presents a key challenge when accounting for elective land use-based activities under the Kyoto Protocol (wetland drainage and rewetting (WDR), cropland management (CM) and grazing land management (GM)), in which current land use-driven greenhouse gas emissions are compared to a reference situation in 1990. This case study is the first to demonstrate the feasibility of using high-resolution land-use proxies from different datasets for Kyoto accounting in a data-rich case study region in Germany. The study region is characterised by organic soils and has been subject to significant nature conservation measures, including land-use changes, reductions in land-use intensity and changes in groundwater table depth. A consistent time series of 20 years of land use with a spatial resolution of 0.01 ha was created from various fine-grained spatial datasets for organic soils in the Drömling nature park by applying a newly developed ⿿translation key⿿. The translation key accounted for systematic differences in legends and thematic resolution. We also tested whether the land-use datasets served as trustworthy proxies for groundwater table depth. Land use in the Drömling nature park became less intensive during the study period of 1992⿿2012. The greatest land-use change (142 ha year ⿿1, 1.14% year ⿿1 ) occurred between 2000 and 2008. This was in line with management measures undertaken in the nature park. The centre of the nature park became wetter and there was an increase in the share of grassland and more natural vegetation types. The groundwater table correlated with land use and land-use intensity on organic soils in the study area throughout the entire period. Land-use changes were accompanied by altered groundwater tables, except for the conversion from cropland to grassland. Our study indicates that detailed land-use time series can serve as a semi-quantitative proxy for groundwater depth, but that any robust quantitative assessment of water table changes requires in situ data, e.g. from a network of dipwells. Therefore, the combination of land-use and dipwell data provided an accurate basis for estimating GHG emission reductions from drained organic soils since 1990, which is the centre of the Kyoto activity WDR, but also part of afforestation/reforestation (AR) and deforestation (D), forest management (FM), CM and GM. Even the detailed land-use time series on its own would fulfil the requirements for WDR accounting, although with considerable uncertainty about the drainage status of the organic soils. We present the study area of organic soils as a showcase for combining the difficult issues of monitoring changes in land-use intensity as well as in soil wetness, the latter being most relevant for organic soils. The methodology is equally applicable to and relevant for mineral soils.